Targeting Rac and Cdc42 GEFs in Metastatic Cancer - Maldonado, Maria del Mar; Medina, Julia Isabel; Velazquez, Luis; Dharmawardhane, Suranganie (Frontiers in Cell and Developmental Biology, 2020)
The Rho family GTPases Rac and Cdc42 have emerged as key players in cancer metastasis, due to their essential roles in regulating cell division and actin cytoskeletal rearrangements; and thus, cell growth, migration/invasion, polarity, and adhesion. Recent studies have established aberrantly expressed/activated Rac and Cdc42 as drivers of metastasis and therapy resistance in multiple cancer types. Rac and Cdc42 are often dysregulated in cancer due to hyperactivation by guanine nucleotide exchange factors (GEFs), belonging to both the diffuse B-cell lymphoma (Dbl) and dedicator of cytokinesis (DOCK) families. Rac/Cdc42 GEFs are activated by a myriad of oncogenic cell surface receptors, such as growth factor receptors, G-protein coupled receptors, cytokine receptors, and integrins; consequently, a number of Rac/Cdc42 GEFs have been implicated in metastatic cancer. Hence, inhibiting GEF-mediated Rac/Cdc42 activation represents a promising strategy for targeted metastatic cancer therapy. Herein, we focus on the role of oncogenic Rac/Cdc42 GEFs and discuss the recent advancements in the development of Rac and Cdc42 GEF-interacting inhibitors as targeted therapy for metastatic cancer, as well as their potential for overcoming cancer therapy resistance.